The effectiveness of a novel optical probe in subgingival calculus detection - A Kasaj (Journal compilation 2008 Blackwell Munksgaard, 2008)
The aim of the present study was to evaluate the effectiveness of a novel optical calculus detection system under in vivo conditions.